SEQUENTIAL EXPLANATORY ANALYSIS OF SCHOOL SUPERVISORS PERFORMANCE REVIEWED FROM ORGANIZATIONAL CULTURE AND WORK MOTIVATION - Idham Khalik, Sofyan, (SJEE (Scientific Journals of Economic Education), 2019)
AbstrakPenelitian ini bertujuan untuk mencari peluang dari sumbangan variabel independen budaya organisasi dan motivasi kerja yang dapat digunakan sebagai alternatif untuk meningkatkan variabel dependen kinerja, melalui pengujian korelasi antara variabel budaya organisasi dan motivasi kerja dengan kinerja, baik secara mandiri maupun simultan. Metode yang digunakan adalah gabungan metode kuantitatif dan kualitatif dengan model metode campuran: sekuensial eksplanatori, yang berarti bahwa urutan penelitian dimulai dengan menggunakan metode kuantitatif dan dilanjutkan dengan penguatan dengan metode kualitatif. Teknik pengambilan sampel dalam penelitian ini menggunakan simple random sampling  dengan jumlah sampel terpilih sebanyak 54 pengawas sekolah. Penelitian ini secara kuantitatif dan kualitatif mengungkapkan bahwa: terdapat hubungan positif yang signifikan antara variabel budaya organisasi dan kinerja pengawas sekolah (r=0,502, p<0,01), ini menunjukkan ada variabel lain yang tidak termasuk dalam model yang dapat mempengaruhi kinerja pengawas sekolah sebesar.Kata Kunci: Budaya Organisasi, Motivasi Kerja, Kinerja Pengawas Sekolah.  AbstractThis research aims to find opportunities from the contribution of independent variables namely organizational culture and work motivation that can be used as an alternative to increase dependent variables namely performance, through testing the correlation between organizational culture variables and work motivation with performance, both independently and simultaneously. The method used is combined of quantitative and qualitative method with mixed methods model: explanatory sequential, that means the sequence of research begins by using quantitative methods continued with strengthening qualitative methods. The sampling technique in this research used simple random sampling with number of selected samples as many as 54 school supervisors. This research quantitatively and qualitatively revealed that: when its tested simultaneously, there was a significant positive relationship between organizational culture variables and work motivation with school supervisor performance, (r=0,545,p<0,01), this indicates there was existence of other variables that not included in the model that can affect the performance of school supervisors2.Keyword : Organizational Culture, Work Mtivation, School Supervisor’s Performance.